1994
DOI: 10.1063/1.112345
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of porous silicon and its correlation with photoluminescence

Abstract: Microstructure of porous silicon (PS) was observed through high-resolution transmission electron microscope to study a relationship between the microstructure and a photoluminescence (PL) from PS. Three PS samples were made through anodization with different current densities. The samples had different PL spectra and were supposed to have different microstructures. Threadlike structures of Si and Si crystallites in the PS layer were observed in all the samples. The threadlike structure has the same density in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…To understand the origin of the visible photoluminescence, the correlation of the sizes of the silicon nanocrystallites with the photoluminescence of porous silicon has been under intensive investigation for about two decades. For an example, blue photoluminescence was reported from oxide-free porous silicon [8], and the electron microscopy data showed that the sizes of individual silicon crystallites in porous silicon films were in the order of several nanometers [3,4]. From the comparison of the optical properties of porous silicon to its microstructures, quantum size effect has been recognized as one of the light-emission mechanisms involved in porous silicon.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To understand the origin of the visible photoluminescence, the correlation of the sizes of the silicon nanocrystallites with the photoluminescence of porous silicon has been under intensive investigation for about two decades. For an example, blue photoluminescence was reported from oxide-free porous silicon [8], and the electron microscopy data showed that the sizes of individual silicon crystallites in porous silicon films were in the order of several nanometers [3,4]. From the comparison of the optical properties of porous silicon to its microstructures, quantum size effect has been recognized as one of the light-emission mechanisms involved in porous silicon.…”
Section: Introductionmentioning
confidence: 98%
“…The report on the visible light emission of porous silicon has aroused strong interest in academia because of the rich physics in this quantum system [1][2][3][4][5][6][7][8]. To understand the origin of the visible photoluminescence, the correlation of the sizes of the silicon nanocrystallites with the photoluminescence of porous silicon has been under intensive investigation for about two decades.…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be understood by the nano-sized crystallites do not uniformly distribute on the PS surface. The size of nano-crystals formed on the PS surface after etching also affects PL energy [11,12]. When the size of nano-crystals decreases, the PL spectrum shifts towards high energy region (blue shift) [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…PS materials have been prepared by a variety of different methods such as photochemical, 1-3 laser annealing 4 and anodization. 5 The electrical properties of photosynthesized PS layer in a PS/n-Si heterostructure has been studied by Ahmed et al 6 ; they found that this structure presents a rectifying junction, confirming a formation of heterojunction. The authors also studied the photovoltaic properties of the Al/PS/n-Si double junction, and they found that the generated photovoltage is due to the co-contribution of the Al/PS Schottky junction and the PS/Si heterojunction.…”
Section: Introductionmentioning
confidence: 95%